The determinants of sovereign bond yield spreads in the EMU - Afonso, António (2012)
We use a panel of euro area countries to assess the determinants of long-term sovereign bond yield spreads over the period 1999.01-2010.12. We find that, unlike the period preceding the global financial crisis, European government bond yield spreads are wellexplained by macro- and fiscal fundamentals over the crisis period. We also find that the menu of macro and fiscal risks priced by markets has been significantly enriched since March 2009, including the risk of the crisis’ transmission among EMU member states, international risk and liquidity risk. Finally, we find that sovereign credit ratings are statistically significant in explaining spreads, yet compared to macro- and fiscal fundamentals their role is limited.